Earth in the holy Qur'an : how to protect and maintain it? - Deuraseh, Nurdeng (2009)
Attempt will be made in this paper to discuss land and soil (earth) in the light of the Holy Qur’an as well as its role in making a healthy environment by protecting and maintaining the land and soil (earth). The land and soil are considered as essential thing for making a healthy environment. According to the Qur’an, the religious duties of man are not only to feed the poor but also to avoid polluting the environment. In other words, what is appreciable in the eyes of God is not only to be kind to human beings, but also to soil and land, air, water, plant, trees and animals, etc. The land and soil have a common characteristic, namely: they may be of continuous benefit to mankind if used wisely. The discussion on this issue will present a timely reminder in relation to the attitude of man towards land and soil (earth). The Holy Qur’an says: وَآيَةٌ لَّهُمُ الْأَرْضُ الْمَيْتَةُ أَحْيَيْنَاهَا وَأَخْرَجْنَا مِنْهَا حَبًّا فَمِنْهُ يَأْكُلُونَ {33} وَجَعَلْنَا فِيهَا جَنَّاتٍ مِن نَّخِيلٍ وَأَعْنَابٍ وَفَجَّرْنَا فِيهَا مِنْ الْعُيُونِ {34} لِيَأْكُلُوا مِن ثَمَرِهِ وَمَا عَمِلَتْهُ أَيْدِيهِمْ أَفَلَا يَشْكُرُونَ {35} “A sign for them is the Earth that is dead: We do give it life and produce grain there from, of which ye do eat. And We produce therein orchards, with date-palms and grapes, and We cause springs to gush forth therein: that they may enjoy the fruit of this (artistry): it was not their hands that made this: will they not then give thanks? (Al-Qur’an, Chapter Yasin (36): 33-35).